Adsorption of heavy metal from wastewater by bioabsorbent modified azolla microphylla and lemna minor - Nasuha Mohamad Nasrol; Noorashikin Md Saleh; Tanusha Devi Elan Solan; Nor Yuliana Yuhana; Farhanini Yusoff; Saliza Asman (Penerbit Universiti Kebangsaan Malaysia, 2024)
Environmental toxicity from rapid industrialization raises concerns about water pollution caused by industrial waste and urban sewage. Aquatic macrophytes, such as the Azolla species, have shown promise in absorbing heavy metals and nutrients from water. This study introduces a novel approach by evaluating Azolla microphylla and lemna minor as an economical adsorbent for copper removal from rivers. Moreover, this study stands out by conducting thorough characterization analyses. The adsorbent material underwent XRD, SEM, BET, and FTIR analyses after being crushed and sieved to 1-2 mm. Copper was extracted from river water using UV-Vis detection at 285 nm. Optimal conditions for adsorption were determined at pH 4, 30 minutes of contact time, and 0.4 g of adsorbent. Copper concentrations in the Sungai Petani, Sungai Selangor, and Sungai Langat ranged from 2 mgL-1 to 5 mgL-1. Azolla proves effective as a copper adsorbent due to its simplicity in sample preparation, time-saving benefits, cost-effectiveness compared to conventional systems, and high copper recovery rate. By successfully removing copper, a prevalent heavy metal contaminant in industrial waste and urban sewage, this research contributes to achieving Sustainable Development Goal 6 for clean and safe water supplies.